Inovasi Pembelajaran Pendidikan Agama Islam Di Era Revolusi Industri 4.0 - Mulyasari, Rini (Jurnal Pendidikan Agama Islam, 2024)
In studying Islamic religious education, we must not ignore technological developments which have a big impact on our lives, whether we realize it or not. SD Negeri 034784 Panji, Dabutar District. Utilizing technological advances to enable learning innovation in Islamic religious education. Examples include teleconferencing, Google Classroom, and Zoom Meeting which use features such as electronic mail (email), mobile phones, MP3 players, websites, blogs, and search engines. Learning models that are developing include electronic learning (e-learning), electronic books (e-books), online courses, online discussions and computer-assisted learning. The use of whiteboards and markers has been replaced by the use of notebooks, LCD projectors, etc. Printed resource books, modules and student worksheets have been replaced by e-books, digital libraries, YouTube and websites. This research focuses on qualitative research using descriptive methods. This research aims to determine the natural role of learning innovation in Islamic religious education in the Industrial Revolution 4.0 era. Primary School Learning SDN 034784 Panji Dabutar Kab. Dairy. This research is suitable for using a qualitative research approach using descriptive methods to reveal facts as empirical truth. Research methodology is the method or procedure for carrying out all research activities. The type of research used in this research is qualitative research with a descriptive approach. Qualitative research is a research method that produces descriptive data in the form of people's written and spoken words and observed behavior. Qualitative research involves the importance of efforts to explore and understand the implications of what happens to different individuals and groups due to social or humanitarian issues. SD Negeri 034784 Panji Dabutar District. In the 2023 and 2024 academic years, we will carry out learning using information technology characterized by the Industrial Revolution 4.0. Teachers continue to perfect current developments by innovating Islamic religious education learning using Industrial Revolution era applications such as Google Classroom, Zoom, and WhatsApp. Participants Students are very happy to study with the help of today's sophisticated information technology during the industrial revolution, but most of them have difficulty attending classes due to financial constraints. "We are actively responding to developments in PAI learning in the 4.0 era, because learning must be adapted to current developments," he said.